If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4y+8=7y-67
We move all terms to the left:
4y+8-(7y-67)=0
We get rid of parentheses
4y-7y+67+8=0
We add all the numbers together, and all the variables
-3y+75=0
We move all terms containing y to the left, all other terms to the right
-3y=-75
y=-75/-3
y=+25
| -4(2a+2)=-16 | | -3x+6=28-4x | | 3a+1/4=a+7/2 | | t/4+9=13 | | 3s+7s=9s+2 | | 2=6-2r | | 5w=6w+9 | | -35x=-34 | | 8y–9=6y+3 | | j/9+57=62 | | 90-x=0.8x | | 7/4x+1/3x=2x+12/3+8/3x | | w/9-2=3 | | 8n2-40n-42=6 | | 2(y-1)^2=72 | | 12z+3+7z=-12 | | 15.6=4.8+.9*t | | 72=12x | | -9/5a=27 | | (.22)x=4176000 | | 8(d+6)=96 | | 16=4(f−75) | | -2+r=4 | | 2.5p=4.8 | | N-17=15+3n+18 | | 6j+2=26 | | 2X^2+33x+100=0 | | 9−2x−9−16x=−14x−7−4x−11 | | x+35x=90 | | 4x+47=8x-13 | | 1/5(20p-15)=2p+4 | | 4+6t=28 |